PHYSICAL MODELING FOR DETERMINATION SLIP PLANE OF LANDSLIDE USING GEOELECTRICAL METHODE - Rahim Achmad; Rohima Wahyu Ningrum; Astuti Salim (ICETIA, 2016)
A physical modeling has been conducted in alaboratory scale, to determine the slip plane oflandslides. The physical model was installedin a container which is filled by landslidematerial (moist silty soil) and massivematerial as the host rock. The layer modelsare consist of six types of landslide situationthen measured by geoelctrical method incentimetre scale. The result of geoelctricalmeasurement showed subsurface image bytheir own resistivity value. The host rockmaterial has a high resistivity (range from:100 to 150 Ωm) value, compared to resistivityvalues of landslide material(range from: 25 to85Ωm). Border of difference layer creates alayer as known as slip plane of landslide.Thegeoelctrical image of subsurface alsomeasured the depth of slip plane.